Menelusuri Hukum Islam: Peran Al Qur’an Dalam Pembentukan Norma Hukum - Rafha Adha Abiyutama; Arif Septian Marta; Rafif Weno Putra; Muhammad Haikal; Robby Ichsan; Fitria Mayasari; Wismanto Wismanto (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Law that is just and in line with social values adopted by society. This role is increasingly relevant in facing modern challenges, where understanding and application of the teachings of the Qur'an have an important role in the formation of legal norms in Muslim society. As a holy book, the Qur'an provides moral and ethical guidelines that form the basis for the Islamic legal system. Through its various verses, the Qur'an establishes the principles of justice, goodness, and social responsibility that influence individual behavior and interactions between members of society. The purpose of this study is to explore the values of Islamic law related to the role of the Qur'an in the formation of legal norms. The method used in this study is a qualitative method, by making books, magazines, articles and journals related to the research theme to collect data, then codify it, and then describe it in this article. The results of this study indicate that the application of Islamic law is largely determined by the Qur'an and Sunnah. Laws taken from sources other than the Qur'an and Sunnah will not last long, because the law is made by humans. So that potentially whoever is in power is the one who determines the law. In addition, the Qur'an also provides concrete rules regarding aspects of life, such as marriage, inheritance, and crime, which are then interpreted and applied in the context of sharia law. Thus, the Qur'an not only functions as a spiritual source, but also as a basis for the formation of norms that need to be adjusted to social dynamics and developing legal needs.